Effective smart rotary parking management in urban areas - Kaci Meziane; Salem Merabti; Zakaria Layate; Hakim Ait Said; Sofiane Amrane; Lydia Terki (The Journal of Engineering and Exact Sciences)
With urbanization on the rise, coupled with the burgeoning intensity of traffic in cities, parking management is becoming an increasingly insurmountable problem. This paper concentrates on the design and development of an intelligent rotary parking, with an appropriable lending function for eight vehicles within a mini urban encroachment. The system combines sensors, servomotors, and an Arduino controller to an automated parking system that saves space by parking vehicles vertically one above another. The proposed solution consists of sensors with an automatic barrier system to allow and control access to vacant parking spaces. To provide more ground parking space with better reliability and lower impact on the environment, the evaluation shows that for urban areas, the system might improve the traffic flow, reduce emissions, and offer a sustainable way of solving problems about parking.